2017
DOI: 10.1111/1462-2920.13690
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes of fungal community shifts driven by tree genotype and spatial‐temporal factors in Mediterranean pine forests

Abstract: Fungi provide relevant ecosystem services contributing to primary productivity and the cycling of nutrients in forests. These fungal inputs can be decisive for the resilience of Mediterranean forests under global change scenarios, making necessary an in-deep knowledge about how fungal communities operate in these ecosystems. By using high-throughput sequencing and enzymatic approaches, we studied the fungal communities associated with three genotypic variants of Pinus pinaster trees, in 45-year-old common gard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 71 publications
6
37
0
Order By: Relevance
“…Differences in litter qualities have been demonstrated at interspecific (Wang et al ., ) and intraspecific levels (Madritch & Hunter, ) and recognized as a consequence of the genetic expression (Allan et al ., ). Litter quality controls litter decay and soil functioning through its effect on the belowground microbial communities (Chavez‐Vergara et al ., ), and these last act, in turn, as important controlling factors of SOM formation and nutrient mobilization (Pérez‐Izquierdo et al ., ). In fact, we observed that enzymes related to hemicellulose degradation and organic N mobilization were particularly active in soil beneath the Atlantic trees, compared with the other genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in litter qualities have been demonstrated at interspecific (Wang et al ., ) and intraspecific levels (Madritch & Hunter, ) and recognized as a consequence of the genetic expression (Allan et al ., ). Litter quality controls litter decay and soil functioning through its effect on the belowground microbial communities (Chavez‐Vergara et al ., ), and these last act, in turn, as important controlling factors of SOM formation and nutrient mobilization (Pérez‐Izquierdo et al ., ). In fact, we observed that enzymes related to hemicellulose degradation and organic N mobilization were particularly active in soil beneath the Atlantic trees, compared with the other genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…season), are among the main environmental factors in the efficiency of C use and ecosystem functioning, directly or indirectly, or both, affecting soil microorganisms (Manzoni et al ., ). Different microbial groups decompose and assimilate C compounds differently depending on their quality (Wang et al ., ), and the functional effects observed in our study might reflect cascading effects on microbial communities (Pérez‐Izquierdo et al ., ), which deserves further analysis. Potential enzyme activities were measured in optimally controlled conditions; therefore, results could vary under field conditions where complex multi‐factor interactions usually occur (Baldrian, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in combination with the sessile nature of trees, may form a “much more intimate (localized) pathogen‐host interaction”, leading to low pathogen‐induced mortality of offspring beneath unrelated conspecifics compared to those beneath their parent trees (Augspurger & Kelly, ). The disease triangle further predicts that intraspecific genetic divergence among host provenances (or “genotypes” in Pérez‐Izquierdo et al, ) and the genetic variation within pathogen populations (e.g. formae speciales in Fusarium oxysporum ; Altinok, Can, & Altinok, ) could cause differential infestation, depending on the co‐occurring genotypes of the host and pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Pines are obligatory ectomycorrhizal (ECM) plants and this intimate relationship strongly influences the surrounding environment (Tarkka, Drigo, & Deveau, ). The effects of the plant genotype on below‐ground microbial communities can be ideally studied through the symbiosis between pines and ECM fungi (Patterson, Flores‐Rentería, Whipple, Whitham, & Gehring, ; Pérez‐Izquierdo et al, ; Piculell, Eckhardt, & Hoeksema, ). Patterson et al () have recently shown that ECM community composition is under strong plant genetic control in Pinus edulis .…”
Section: Introductionmentioning
confidence: 99%